Psychological stress and psoriasis: a systematic review and meta‐analysis. (16th May 2018) - Snast, I.; Reiter, O.; Atzmony, L.; Leshem, Y.A.; Hodak, E.; Mimouni, D.; Pavlovsky, L.
Summary: Psoriasis is a chronic inflammatory skin disease. It is common knowledge among patients with psoriasis and their physicians that psychological stress worsens the disease; however, there is a lack of robust evidence to prove this linkage. This review examined studies evaluating the interaction between preceding psychological stress and psoriasis worsening and onset. The authors reviewed 39 different studies that included 32, 537 patients with psoriasis. The first type of studies evaluated psoriasis patients at a specific point in time. They found that approximately half the patients believed that stress worsened their disease and could remember stressful events before the onset or worsening of psoriasis. However, these studies contributed poor evidence for a significant link between stress and psoriasis as the patients were not compared to a control group (people without psoriasis exposed to stressful events), and it was unclear how much time passed between psoriasis worsening/onset and patients' recall of the events. The second type of studies evaluated the frequency at which patients with psoriasis remembered stressful events before the onset or worsening of their disease compared to people without psoriasis. These studies gave contradictory results ‐ some found that psoriasis patients more frequently recalled stressful events compared to people without psoriasis while other studies found no significant differences. Interestingly, the only study that was not based on patients' memories but reviewed documented diagnosis of stress disorder, found similar rates between patients with psoriasis and people without psoriasis. The third approach, in one study, evaluated the interaction between stress levels at one point in time and psoriasis severity one month later, finding only a slight link. The authors found no strong evidence to support the belief that preceding psychological stress strongly links with psoriasis worsening and onset. More research, especially studies that record psychological stress and evaluate disease severity over time, are needed to better understand the influence of psychological stress on psoriasis onset and severity. Abstract : Linked Article:  Snast et al. Br J Dermatol 2018;178 :1044–1055